1976
DOI: 10.1136/jnnp.39.10.990
|View full text |Cite
|
Sign up to set email alerts
|

Computerised axial tomography in patients with severe migraine: a preliminary report.

Abstract: S Y N 0 P S I S Patients suffering from severe migraine, usually for many years, have been examined by the EMI scanner between attacks. Judged by criteria validated originally by comparison with pneumoencephalography, about half of the patients showed evidence of cerebral atrophy. Perhaps of more significance than generalised atrophy was the frequency of areas of focal atrophy and of evidence of infarction.Although migraine is a common disease afflicting between 5% and 10% of the population (Friedman, 1971), l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
1
2

Year Published

1980
1980
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(46 citation statements)
references
References 6 publications
(5 reference statements)
0
43
1
2
Order By: Relevance
“…2,8,[15][16][17][18][19][20][21][22][23] The populations in these studies were reasonably similar. Results from these studies were combined in a meta-analysis to yield a summary prevalence of 0.0018 (approximately 0.2%), with an upper 95% confidence limit of 0.0059 (approximately 0.6%).…”
Section: Nonacute Headache and Normal Neurological Examinationmentioning
confidence: 61%
“…2,8,[15][16][17][18][19][20][21][22][23] The populations in these studies were reasonably similar. Results from these studies were combined in a meta-analysis to yield a summary prevalence of 0.0018 (approximately 0.2%), with an upper 95% confidence limit of 0.0059 (approximately 0.6%).…”
Section: Nonacute Headache and Normal Neurological Examinationmentioning
confidence: 61%
“…Prensky [16] has postulated that the per sistent focal activity on EEG between episodes in migraine patients is indi cative of permanent brain damage, and both Verret and Steele [15] and Hosking et al [9] reported persistent EEG changes in their patients with resi dual neurologic deficits. In support of the concept of permanent CNS injury following migraine, Hungerford et al [14] performed CT scans in 53 patients with long-standing migraine and demonstrated generalized or focal atrophy in 14 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Connor [13] reported on 18 patients, in cluding several teenaged patients with permanent neurologic deficits follow ing complicated migraine attacks. More recently, Hungerford et al [14] de tected abnormalities on neurologic exam in 13 of 30 patients with long histo ries of complicated migraine..…”
Section: Discussionmentioning
confidence: 99%
“…2 ' 6 Angiography is usually normal, but some cases show occlusion of one of the major cerebral arteries, most commonly the P.C.A. 4 ' 5 7 However, given the high prevalence of migraine, 15 to 30% of all stroke patients would be expected to have a past history of migraine. Therefore, to causally link cerebral infarcts to migraine itself, three criteria are thought to be essential.…”
Section: Discussionmentioning
confidence: 99%